2020
DOI: 10.1530/rep-19-0401
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone-induced RNA Hand2os1 regulates decidualization in mice uteri

Abstract: Decidualization is a critical process for successful embryo implantation and subsequent placenta formation. The characterization and physiological function of lncRNA during decidualization remain largely unknown. In the present study, we conducted RNA-sequencing analysis to compare gene expression between decidua of days 6 and 8, and normal pregnant endometrium (day 4). A total of 2332 high-confidence putative lncRNA transcripts were expressed. Functional clustering analysis of cis and trans lncRNA targets sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The lncRNA DNM3OS sponged miR-126 to affect cell proliferation and apoptosis by regulating IGF1, by binding to the promoter of miR-126 in CHON-001 cells [64]. The expression level of the lncRNA HAND2OS1 was higher on day 4 of pregnancy than day 1 of pregnancy, while the level increased dramatically on day 6, which is similar to the findings of this study, where two transcripts of the lncRNA HAND2OS1 were downregulated at E0.5 [65]. Ankyrin repeat domain protein (ANKRD) is a large family of proteins including enzymes, transcription factors, and membrane receptors, which are composed of multiple copies of ankyrin repeat (AR) with a 33-amino-acid motif [66].…”
Section: Discussionsupporting
confidence: 88%
“…The lncRNA DNM3OS sponged miR-126 to affect cell proliferation and apoptosis by regulating IGF1, by binding to the promoter of miR-126 in CHON-001 cells [64]. The expression level of the lncRNA HAND2OS1 was higher on day 4 of pregnancy than day 1 of pregnancy, while the level increased dramatically on day 6, which is similar to the findings of this study, where two transcripts of the lncRNA HAND2OS1 were downregulated at E0.5 [65]. Ankyrin repeat domain protein (ANKRD) is a large family of proteins including enzymes, transcription factors, and membrane receptors, which are composed of multiple copies of ankyrin repeat (AR) with a 33-amino-acid motif [66].…”
Section: Discussionsupporting
confidence: 88%
“…49 The expression of lncRNA Hand2os1 is induced by P4 in a PR-dependent manner during decidualization, and the use of a PR antagonist abolishes P4-induced Hand2os1 expression. 52 In this study, we found that BMPR1B-AS1 was up-regulated during decidualization in vitro. knockdown of BMPR1B-AS1 inhibited the expression of decidualization marker molecules and reversed the MET process, which prevented hESCs from maintaining the decidualization-specific morphology induced by cAMP and MPA.…”
Section: Discussionmentioning
confidence: 56%
“…In endometrial lncRNA expression profiles, there were differences between patients with recurrent failure of implantation and normal women, suggesting a tight relationship between lncRNA and endometrial receptivity 49 . The expression of lncRNA Hand2os1 is induced by P4 in a PR‐dependent manner during decidualization, and the use of a PR antagonist abolishes P4‐induced Hand2os1 expression 52 . In this study, we found that BMPR1B‐AS1 was up‐regulated during decidualization in vitro.…”
Section: Discussionmentioning
confidence: 56%
“…The expression of many lncRNAs is upregulated during decidualization, such as NEAT1 , RP11-627G23.1 , and PSORS1C3 , but their function in this process remains to be elucidated [ 25 ]. These lncRNAs may regulate the expression of genes associated with cell proliferation, differentiation, migration, and angiogenesis during decidualization, as proposed in mice uteri [ 189 ]. PTENP1 , a lncRNA that is highly expressed in the luminal epithelium during the mid-secretory phase, regulates the expression of several miRNAs to promote the implantation process [ 173 ] (Fig.…”
Section: Non-coding Rnasmentioning
confidence: 99%